Preoperative deltoid assessment by contrast-enhanced ultrasound (CEUS) as predictor for shoulder function after reverse shoulder arthroplasty: a prospective pilot study - Fischer, Christian; Flammer, Sophie; Kauczor, Hans-Ulrich; Zeifang, Felix; Schmidmaier, Gerhard; Kunz, Pierre (Archives of orthopaedic and trauma surgery, 2020)
Although the deltoid represents the main motor muscle after reverse shoulder arthroplasty (RSA), its standardized preoperative assessment regarding morphology and function is still not established. Its clinical relevance and interactions with major biomechanical parameters like the medialization of the center of rotation (COR) regarding shoulder function after RSA are yet unknown. We evaluated contrast-enhanced ultrasound (CEUS) of the deltoid as possible surrogate marker for individual deltoid properties of patients receiving an RSA, and its predictive value for postoperative shoulder function.
Published online: 17 October 2019
Gesehen am 11.11.2020